Microtus xanthognathus - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Microtus xanthognathus (Leach, 1815). Zool. Mise., 1:60. TYPE LOCALITY: Canada, Manitoba, Hudson Bay. DISTRIBUTION: Western boreal taiga zone: EC Alaska to W Northwest Territories, southeastwards to C Alberta and western coast of Hudson Bay, Canada. COMMENTS: Relationships obscure: probably not a sister species to M. chrotorrhinus as once believed (see that account and Lidicker and Yang, 1986); placed by Zagorodnyuk (1990) in the subgenus Aulacomys, richardsoni species group. Karyotype reported and affinities discussed by Rausch and Rausch (1974). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 531, DOI: 10.5281/zenodo.7353098